Old Age before Modernity Case Studies and Methodological Perspectives, 500 BC ‒ 1700 AD - Neumann, Christian Alexander (Online-Schriften des DHI Rom. Neue Reihe Pubblicazioni online del DHI Roma. Nuova serie, 2023)
This book investigates old age and ageing in premodern times, with a special focus on the Middle Ages. Perspectives from gerontology and the humanities, and above all from history, are combined to provide novel insights. The gerontological articles explain key theories and methods that are relevant for the analysis of historical developments, while the contributions from the humanities offer historical evidence complementary to these inputs.